2024
DOI: 10.3389/fnut.2024.1373799
|View full text |Cite
|
Sign up to set email alerts
|

The effect of last meal “Suhoor” timing on diurnal variations in cognitive performance during Ramadan fasting among female athletes

Houda Bougrine,
Achraf Ammar,
Khaled Trabelsi
et al.

Abstract: The present study aimed to investigate the effect of the timing of the last meal, “Suhoor”, on diurnal variation in cognitive performance during Ramadan intermittent fasting (RIF). In a randomized order, 26 adolescent female athletes (aged 15.9 ± 0.9 y) were tested in three sessions at 7:00 a.m., 12:00 p.m., and 5:00 p.m. across four different conditions: the 10 days preceding Ramadan (PR); the final 12 days of Ramadan (RO): two different conditions: Early Suhoor (SEarly), and Late Suhoor (SLate); and, ultimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…While engaging in sports and exercise during RIF has been related to various benefits for physical, mental, and spiritual well-being, as well as community involvement, it has been also associated with various risks of dehydration, low blood sugar, fatigue, and delayed recovery ( 9 ). Furthermore, previous data did not support the association of RIF with any changes in dietary intake in both male ( 10 ) and female athletes ( 2 , 11 ). However, an athlete's capacity to focus their cognitive resources on internal or external stimuli plays a pivotal role in achieving success particularly in team ball sports.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…While engaging in sports and exercise during RIF has been related to various benefits for physical, mental, and spiritual well-being, as well as community involvement, it has been also associated with various risks of dehydration, low blood sugar, fatigue, and delayed recovery ( 9 ). Furthermore, previous data did not support the association of RIF with any changes in dietary intake in both male ( 10 ) and female athletes ( 2 , 11 ). However, an athlete's capacity to focus their cognitive resources on internal or external stimuli plays a pivotal role in achieving success particularly in team ball sports.…”
Section: Introductionmentioning
confidence: 78%
“…The decline in cognitive skills related to RIF could be partially explained by the lack of or inadequate predawn meal (Suhoor or Sahour) timing, quantity, and/or quality among athletes. Recent findings in female athletes indicate the association between nutrition timing during RIF and the variation in cognitive ( 2 ) and physical ( 52 ) performance throughout the day, particularly at midday and in the afternoon. A late last pre-dawn meal was advantageous to preserve better cognitive and physical performance in the morning and prevent any decrease during the midday or afternoon fast.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, previous studies that were conducted among female athletes demonstrated better performance during afternoon sessions concerning short-term high-intensity performance (Bougrine et al, 2022;Graja et al, 2020;Oleka, 2020). In this context, previous studies revealed that cognitive and high-intensity physical performance among female athletes depend of time of day with improvements observed in the afternoon (Bougrine et al, 2022;Bougrine et al, 2023;Bougrine et al, 2024). Nonetheless, during the past few decades, women's participation in physical activity and sports has increased substantially.…”
Section: Introductionmentioning
confidence: 96%